A longitudinal study of MNE innovation: the case of Goodyear. Issue 3 (9th September 2014) - Giada Scalera, Vittoria; Mukherjee, Debmalya; Perri, Alessandra; Mudambi, Ram
Abstract : Purpose: – The purpose of this article is to provide insights into the innovation trajectory, and knowledge pipelines of mature industry multinational enterprises (MNEs). The ability to innovate constantly amidst a turbulent and competitive environment is often the key force behind MNE survival and dominance. Design/methodology/approach: – This study conducts an in-depth longitudinal study of the Goodyear Tire and Rubber Company, a global manufacturing company in the tire and rubber industry. The findings are based on USPTO patent and trademark data from 1975-2005. Findings: – The analysis reveals three crucial trends: the major role of continuous investment in innovation in the firm's survival and turnaround; the evolution of the firm's innovation network from a headquarters-centric model toward more geographical dispersal; and the changing mix of innovation from traditional "hard" science-based research toward a greater emphasis on "softer" competencies in design and trademarks. This third trend, in particular, opens up important new avenues for research on MNE innovation practices. Originality/value: – This study integrates historical analysis of a single firm in the context of its changing industry environment. The historical analysis is enriched by a detailed longitudinal quantitative analysis using a variegated dataset of patents and trademarks to investigate innovation.